2008
DOI: 10.1248/cpb.56.443
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interactions of Kaempferol and Quercetin with Intravenous Immunoglobulin by Fluorescence Quenching, Fourier Transformation Infrared Spectroscopy and Circular Dichroism Spectroscopy

Abstract: Initially used as replacement therapy for patients with primary and secondary immune deficiencies, intravenous immunoglobulin (IVIG), the human serum immunoglobulin (Ig) fraction that is mainly composed of normal human polyclonal IgG obtained from plasma pools from a large number of healthy blood donors, is now widely used for the treatment of a large number of autoimmune and systemic inflammatory diseases. 1,2) Recently, great attention has been paid to IVIG potential use as adjuvant anti-neoplastic agent.3-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…However, recent studies have shown that the downregulation of annexins in certain types of malignant cancers is mainly attributable to epigenetic regulation by DNA methylation and histone acetylation, and to deletion of the annexin genes due to chromosomal instability following malignant transformation (Lim & Pervaiz, 2007). In esophageal epithelial carcinoma cells, nuclear annexin A1 is increased by its translocation from the cytosol, and cytosolic annexin A1 is consequently decreased (Liu et al, 2008). Therefore, it is proposed that nuclear annexin A1 rather than cytosolic annexin A1 is more closely associated with cell transformation, namely, cancer initiation¸ while changes of annexin A1 expression may not be involved in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that the downregulation of annexins in certain types of malignant cancers is mainly attributable to epigenetic regulation by DNA methylation and histone acetylation, and to deletion of the annexin genes due to chromosomal instability following malignant transformation (Lim & Pervaiz, 2007). In esophageal epithelial carcinoma cells, nuclear annexin A1 is increased by its translocation from the cytosol, and cytosolic annexin A1 is consequently decreased (Liu et al, 2008). Therefore, it is proposed that nuclear annexin A1 rather than cytosolic annexin A1 is more closely associated with cell transformation, namely, cancer initiation¸ while changes of annexin A1 expression may not be involved in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller bundles were made up of straight single filaments with an average diameter of 4 nm in agreement with the hydrodynamic size of unassembled MAb monomers measured by dynamic light scattering (not shown). FTIR and Raman spectroscopy, which are sensitive to the secondary structure of proteins (35,36), suggested that the assembly of MAb does not feature a significant change in secondary structure before and after the addition of citrate (not shown).…”
Section: Citrate Mediates the Formation Of Stiff And Rigid Mab Filamentsmentioning
confidence: 99%
“…2 and the quenching data collected from the good linear relationship with P < 0.05 are listed in Table 3 [23]. All of the current values of K q are much greater than that of K q(max) (2.0 Â 10 10 M À1 s À1 ), the maximum quenching rate constant of bimolecular diffusion collision, which are indicative of static types of quenching mechanisms arisen from the formations of dark complexes between the fluorophores and quenching agents [50,51]. The EtBr-DNA quenching results also indicate that most of the EtBr molecules have been displaced from EtBr-DNA complex by every quencher at the approximate titration end point and that the intercalation takes place between the compound with DNA [26].…”
Section: Etbr-dna Quenching Assaymentioning
confidence: 92%
“…In the present study, the chelation between phenolic hydroxyl group and carbonyl group of 2-hydroxybenzoylhydrazine side chain of ligand 1b with free Fe 2+ (as catalyst [30]) in iron-EDTA reaction system may make the concentration of free Fe 2+ much lower so that the catalysis becomes very poor and the OH Å formation has been suppressed, thus the inhibitive effect of 1b detected for OH Å is higher than those of other ligands. On the other hand, the values of IC 50 with a notably different order of 2c < 2a < 2b. These results suggest that there are different mechanisms between scavenging or inhibiting OH Å and O ÀÅ 2 , which should be further studied in the future work.…”
Section: Fluorescence Spectroscopy Studymentioning
confidence: 97%